Factors associated with TNF-alpha levels in patients with indirect inguinal hernia: A cross-sectional study. (June 2022) - Warsinggih,; Ulfandi, Devby; Fajar, Amir; Faruk, Muhammad
Abstract: Introduction: Risk factors associated with inguinal hernia include a patent processus vaginalis due to an obliteration failure, defects in the transversalis fascia, increased intra-abdominal pressure, smoking, malnutrition, genetic factors, connective tissue defects and impaired collagen metabolism. Type I collagen predominates in the fascia, which plays a key role in the development of an inguinal hernia. Molecularly, the production of abnormal matrix components or increased inflammatory mediators in collagen such as TNF-α has a very important role in the occurrence of inflammation in inguinal hernias. The study aimed to determine the factors associated with TNF-alpha levels in patients with indirect inguinal hernias. Methods: We evaluate the effect of TNF-α on the anterior rectus sheath tissue collagen in 46 patients with indirect inguinal hernia using a cross-sectional study design. The ELISA method was used to evaluate the levels of collagen TNF-α. We used ANOVA, Pearson's correlation test, and Spearman's correlation test to determine which results were statistically significant, defined by a p-value < 0.05. Results: Body mass index (BMI) average results were 25.7 kg/m 2 . Mean clinical onset was 70.13 months across 46 samples. TNF-α levels and BMI were correlated (p = 0.009). The TNF-α levels in the clinical-grade group (p = 0.044) and the clinical onset group (p = 0.047) varied according to ANOVA. Conclusion: Clinical onset, BMI, clinical grade of indirect inguinal hernia, and TNF-α levels have a significant relationship. Highlights: Several risk factors are associated with inguinal hernia. TNF-α inhibits the synthesis of structural components, which lowers extracellular matrix deposition. TNF-α inhibits type I collagen gene expression by TGF-β, disrupting the structure and strength of the abdominal wall. Clinical onset, body mass index, and clinical grade of indirect inguinal hernia all significantly correlate with TNF-α levels. Age and occupational group do not have a significant relationship with TNF-α levels.